2020
DOI: 10.1111/caim.12370
|View full text |Cite
|
Sign up to set email alerts
|

Managing innovation performance: Results from an industry‐spanning explorative study on R&D key measures

Abstract: Research on R&D performance measures applied in firms is still scarce. Based on the established "R&D laboratory as a system" thinking, systematically derive and identify R&D department level key performance measures. Through a mixedmethod approach, grounded in (1) literature and (2) text analysis, 154 R&D performance measures were developed. Amongst those, an (3) online expert survey, as well as (4) three independent focus group workshops with >40 industry experts from more than ten industries identified and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Additionally, in line with the findings of Angerer et al [32], this study found that financial data is one of the investors' main motivations. Along with the few key performance indicators described in available research, this study's interviewees underscored the importance of efficiency to generate the expected revenues, as financial performance measures are scarce for innovation activities [66].…”
Section: Discussion Implications and Limitationsmentioning
confidence: 99%
“…Additionally, in line with the findings of Angerer et al [32], this study found that financial data is one of the investors' main motivations. Along with the few key performance indicators described in available research, this study's interviewees underscored the importance of efficiency to generate the expected revenues, as financial performance measures are scarce for innovation activities [66].…”
Section: Discussion Implications and Limitationsmentioning
confidence: 99%
“…Measuring the impact of research and development or innovation activities proves difficult (Bican and Brem, 2020). Commonly, innovation managers turn to patent analytics (e.g., Pavitt, 1985; Arundel and Kabla, 1998; Hall et al, 2005).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As a result, it was possible to identify 28 empirical studies which were compared according to their objectives, analytical structures for proposing innovation indicators and metrics, methodological approaches, and methods adopted. Then, focusing more specifically on methodological issues, it can be concluded that among the 28 studies, 15 adopted the scorecard approach (Kerssens-van-Drongelen and Cook, 1997;Wong, 2001;Verhaeghe and Kfir, 2002;Godener and Soderquist, 2004;Bremser and Barsky, 2004;Ojanen and Vuola, 2006;Gama et al, 2007;Chiesa and Frattini, 2009;Lazzarotti et al, 2011, Mohamed, 2013Dewangan and Godse, 2014;Spanò et al, 2016;Zhang, 2016;Bican and Brem, 2020;and Dudic et al, 2020).…”
Section: Exploratory and Descriptive Phasementioning
confidence: 99%
“…To complement the comparative analysis of five established innovation management models, a literature search was conducted, focusing more specifically on previous studies that had employed the systematic literature review (SLR) approach to investigate this research field. This search has yielded several reviews, but only three were selected as an initial step of the literature review: Adams et al, 2006;Dewangan and Godse, 2014;and Bican et al, 2020. An indepth analysis of these articles, including backward citation search and a new search in the Scopus, Web of Science databases, made it possible to identify 28 empirical studies, presented in Table 2.2. They were compared according to their analytical structures for proposing innovation indicators and metrics, methodological approaches, and methods adopted.…”
Section: Innovation Capacity and Performance Measurement Models: Empirical Studiesmentioning
confidence: 99%
See 1 more Smart Citation